Modulatory Role of PYY in Transport and Metabolism of Cholesterol in Intestinal Epithelial Cells - Grenier, Emilie; Garofalo, Carole; Delvin, Edgard; Levy, Emile (PLOS ONE, 2012)
Background Gastrointestinal peptides are involved in modulating appetite. Other biological functions attributed to them include the regulation of lipid homeostasis. However, data concerning PYY remain fragmentary. The objectives of the study were: (i) To determine the effect of PYY on intestinal transport and synthesis of cholesterol, the biogenesis of apolipoproteins (apos) and assembly of lipoproteins and (ii) To analyze whether the effects of PYY are similar according to whether cells are exposed to PYY on apical or basolateral surface. Methodology/Principal Findings Caco-2/15 cells were incubated with PYY (1–36) administered either to the apical or basolateral medium, at concentrations of 50 or 200 nM for 24 hours. De novo synthesis of cholesterol, cholesterol uptake, and assembly of lipoproteins were evaluated through the incorporation of [14C]-acetate, [14C]-cholesterol, and [14C]-oleate, respectively. Biogenesis of apos (A-I, A-IV, E, B-48 and B-100) was examined by the incorporation of [35S]-methionine. The influence of PYY on protein and mRNA levels of many key mediators of lipid metabolism was analyzed by Western blot and PCR, respectively. Our results show that PYY influenced cholesterol metabolism in Caco-2/15 cells depending on the site of PYY delivery. Apical addition of PYY significantly lowered the incorporation of [14C]-cholesterol likely via the reduction of NPC1L1, stimulated intracellular cholesterol synthesis probably through an increase in SREBP-2 expression, whereas it concomitantly increased apo A-I synthesis and decreased LDL secretion. In contrast, basolateral PYY reduced the production of chylomicrons (CM) as well as the biogenesis of apos B-48 and B-100, while lowering the expression of the transcription factors RXRα and PPAR(α,β). Conclusions/Significance PYY is capable of influencing cholesterol homeostasis in intestinal Caco-2/15 cells depending on the site delivery. Apical PYY was able to decrease cholesterol uptake via NPC1L1 downregulation, whereas basolateral PYY diminished CM output through the biogenesis decline of apos B-48 and B-100.